2018
DOI: 10.1186/s40634-017-0119-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in evaluation and treatment of lateral patellar instability

Abstract: Recent years have been characterized by an ongoing increase in knowledge about the different conditions associated with lateral patellar instability. This increase in knowledge provides differentiated approaches to the various pathologies of the patellofemoral joint. Though current guidelines consider medial patellofemoral ligament (MPFL) reconstruction the basic treatment for the unstable patella, medial soft tissue–stabilizing procedures should not be interpreted as stand-alone procedures in every case. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 71 publications
(104 reference statements)
1
27
1
Order By: Relevance
“…Patients with recurrent dislocation typically have abnormalities of knee anatomy and soft tissue integrity, with substantial inter‐subject variability. Clinical interventions that are tailored to the anatomy and mechanics of the individual patient may have benefit in optimizing post‐operative joint stability …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with recurrent dislocation typically have abnormalities of knee anatomy and soft tissue integrity, with substantial inter‐subject variability. Clinical interventions that are tailored to the anatomy and mechanics of the individual patient may have benefit in optimizing post‐operative joint stability …”
mentioning
confidence: 99%
“…Clinical interventions that are tailored to the anatomy and mechanics of the individual patient may have benefit in optimizing post-operative joint stability. [23][24][25] Patients with persistent symptoms of patellar instability are candidates for surgical interventions, with treatment options that include MPFL reconstruction, tibial tubercle osteotomy, sulcus-deepening TP, or combinations of these procedures. 1,[26][27][28] However, currently, there is no universally accepted algorithm for choosing the appropriate procedure(s) for a particular individual.…”
mentioning
confidence: 99%
“…This may have been caused by factors such as the study design, demographic characteristics, intervention treatments, followup duration, and even the scoring system itself. Kujala score is the most commonly used method to evaluate patellofemoral joint disease in recent years [12]. Whereas, there is a growing debate about whether the scoring adequately reflects the complexity of patellar instability [34].…”
Section: Efficacy Evaluationmentioning
confidence: 99%
“…Whereas, there is a growing debate about whether the scoring adequately reflects the complexity of patellar instability [34]. A new assessment score called the Norwich Patellar Instability score has been implemented to overcome the weakness of the Kujala score [35] and it is recommended for use in future studies [12]. In addition, Bitar et al concluded that the Kujala score was significantly increased by MPFL reconstruction [25].…”
Section: Efficacy Evaluationmentioning
confidence: 99%
See 1 more Smart Citation